Optimised routing algorithm in low Earth orbit satellite networks. (25th March 2021) - Ghaith, Izzat; Hussein, Mohammed
To meet the massive growth in demand for multimedia services on mobile devices and to support connectivity anywhere on the planet, it is expected that satellite networks in general and the low Earth orbit (LEO) satellite, in particular, will play a fundamental role in the deployment of these systems. However, LEO satellite groups such as Iridium are too expensive to deploy and maintain. Therefore, extending their service lifetime has emerged as a significant challenge for researchers. The main note in this paper is that one can significantly increase the service life of the satellites by managing the depth of discharge (DoD) of their batteries. Satellites in low Earth orbit groups can spend about 30% of their time under the shadow area, where satellites are powered by batteries. In this paper, we present a new routing metric that rout traffic over satellites exposed to the sun as opposed to the eclipsed satellites.